Design methodology in the French architecture - Takács, Ágnes; Laurent, Cédric (Design of Machines and Structures, 2023)
In this paper the authors are focusing on Jean Nouvel, a significant member of the French architect society. The aim of this research was to analyse the most remarkable elements of the architect’s life’s work: what kind of notable results he created, what ideas did he apply, etc. The authors tried to make a comparison between the design ways of architecture and mechanical engineering.